Pendidikan Agama Kristen dalam Perspektif Teori Perkembangan Iman James W. Fowler: Christian Religious Education in the Perspective of the Theory of Faith Development by James W. Fowler - Esti R. Boiliu (Sekolah Tinggi Teologi Baptis Indonesia, 2021)
James W. Fowler's theory of faith development plays a role in seeing the growth of human faith in God. In this case, Fowler formulated several stages in developing one's faith, including the steps of the faith development of several people who have different beliefs. This study raises the thoughts of James Fowler and its relevance to Christian Religious Education today so that this research results in an understanding that in the context of Christian Religious Education, the development of faith needs to be instilled in students from an early age by educators. The method used in this paper is the literature study method.